On the Uniqueness of Best Simultaneous Approximations in Finite-Dimensional Subspaces - Mshvidobadze, Natia (Journal of Educational Research and Policies, 2026)
This study explores the uniqueness of best simultaneous approximation of two continuous functions on a closed interval from a finite dimensional subspace. The uniqueness condition is demonstrated to imply that the subspace is Chebyshev. The research examines special case of even and odd function approximations, providing valuable insights into the approximation behavior from finite- dimensional spaces.